Kombinasi Metode ADDIE Dan CBL Dalam Merancang Aplikasi Pembelajaran Kimia Pada Sekolah Menengah Atas - Sihotang, Marta Nofita (Jurnal Sains dan Teknologi Informasi, 2024)
Learning is a process of interaction between students and educators and learning resources in a learning environment that includes teachers and students exchanging information. Learning is also a process to help students learn well. In the context of education, the teacher teaches a lesson so that students can learn and master the content of the lesson to achieve a specified objective, can also influence changes in attitudes, as well as the skills of a learner, but this teaching process gives the impression of only being the work of one party, namely the work of teacher only. The ADDIE and CBL methods are methods used to design a computerized and multimedia-based learning application. In addition to the CBI, CAI, and other learning methods, the ADDIE and CBL methods are also suitable methods for use in learning systems that will make it easier for teachers to convey material. One way of computer-assisted learning is the application of the ADDIE and CBL methods. The ADDIE method is a learning system design model that shows the basic stages of a learning system that are simple and easy to learn. While the CBL method is learning that fully uses a computer. In the process of computer-assisted learning, where the computer is used for the purpose of presenting learning in the form of tutorials, simulations and games. This can really help students to be able to implement a learning while playing system that is very effective for the learning process for students.